Successful eradication of leptomeningeal plasma cell disease. Issue 7 (3rd July 2018) - Bruserud, Øyvind; Hansen, Bent-Are; Vetti, Nils; Johansen, Silje; Reikvam, Håkon
Abstract: Plasma cell leukaemia (PCL) is a rare and aggressive form of malignant monoclonal gammopathy characterized by the presence of high levels of plasma cells in peripheral blood. Central nervous system involvement of PCL has no established treatment and an extremely poor prognosis. We here present a 59-year-old male patient diagnosed with PCL, initially treated with induction chemotherapy followed by autologous peripheral blood hematopoietic stem cell transplantation. After achieving a partial response, he relapsed and presented with leptomeningeal disease. He was then successfully treated with dexamethasone, pomalidomide, and an intrathecal combination of methotrexate, methylprednisolone and cytarabine. This cleared his cerebrospinal fluid from plasma cells achieving a durable partial response.